The Role of Digitalization for Entrepreneur in Lontar Village - Putri, Solehatin Ika; Pertiwi, Widya Nur Bhakti; Widikusyanto, Muhammmad Johan; Adiwijaya, Edwin Perdana (MOVE: Journal of Community Service and Engagement, 2024)
Lontar Villages in Tangerang Regency with various potentials including marine fisheries and agriculture. The results of community fishing and farming activities are usually sold directly to middlemen so that the profits obtained by the community are less than optimal. Lontar village communities who still lack knowledge and skills in marketing their business need assistance in utilizing digital media. Most people have cellphones and an internet network. Based on these shortcomings and potential, this article aims to determine the role of digitalization for entrepreneurship in Lontar village. The implementation method is carried out through stages (1) Planning and preparation (2) Implementation of workshops and training (3) Evaluation. The result of this training is that the role of digitalization in theory for entrepreneurship is very important. As for its application to community businesses, it is used to improve the marketing of its products and to obtain better profits from these economic activities. The results can be used to focus the use of certain social media that are relevant to the target market.